A inspeção escolar em Alagoas pós LDB no 9394/96: um instrumento de controle do Estado ou uma instância de avaliação? - Costa, Maria José Alves (2009)
The inspection as a tool of control has always existed in social activities and its various ventures. As achievement, the School Inspection born as a need also to the teaching Tuesday its control, initially exercised by the Church and, with the loss of the influence of religion on education, then power should be exercised by the state public. In the current context, as LDBEN No 9394/96, the function of regulatory and inspection is being the State Councils of Education within each system, a regulatory, responding from whom is positioned to Inspection is the problem of this research, that aims to understand their functions, size and through these practices and their contribution to training in Sydney with the quest to answer the aspirations of society. The theoretical contributions range from a conceptual approach, permeated by year assessment and planning, tools inherent in the inspection process in the regulatory practices of educational institutions in the development of public policies in education. These have direct involvement in educational practices and sedimentary triggered inside the institutions and inexorably in educational indicators reflect the state of Alagoas. The qualitative research was designed as a case study, with the participants, at random, inspectors of the State System of Higher Education and Alabama, using as instruments for collecting data on a semi-structured interviews, observation and documentary research and literature. Experience confirms and intensifies from LDBEN nº 9394/96, the work of inspection as an evaluative, but also the character of precípuo tool against the state, which takes as reference the standards expressed by senior regulator, the State Board of Education and pointing needs to better framework conditions for meeting the demands of the legal framework, management and teaching.